My idea in your head vs Your idea in my head - Griffith-Bourn, Mary Margaret (My University, 2019)
My idea in your head vs Your idea in my head The objective of this discussion is to delve into a cross-cultural communicative context. There is something uniquely human about the evolution of knowledge though communication. While this is seemingly a universal concept, our focus will move from what is universal about communication to what is distinctly unique about the way two languages differ in similar contexts. What happens when there is a discursive clash between the languages? The underlying theories will uncover some of the main ingredients to proper discourse.
Ponencia
Keywords: Bilingüismo; Metacognición; Bilingualism; Cross cultural comparison English/Spanish; Linguistic relativity; Metacognition